Burden of gastrointestinal disease in the United States: 2012 update - Peery, Anne F; Dellon, Evan S; Lund, Jennifer; Crockett, Seth D; McGowan, Christopher E; Bulsiewicz, William J; Gangarosa, Lisa M; Thiny, Michelle T; Stizenberg, Karyn; Morgan, Douglas R; Ringel, Yehuda; Kim, Hannah P; et al. (Gastroenterology (New York, N.Y. 1943), 2012)
Gastrointestinal (GI) diseases account for substantial morbidity, mortality, and cost. Statistical analyses of the most recent data are necessary to guide GI research, education, and clinical practice. We estimate the burden of GI disease in the United States. We collected information on the epidemiology of GI diseases (including cancers) and symptoms, along with data on resource utilization, quality of life, impairments to work and activity, morbidity, and mortality. These data were obtained from the National Ambulatory Medical Care Survey; National Health and Wellness Survey; Nationwide Inpatient Sample; Surveillance, Epidemiology, and End Results Program; National Vital Statistics System; Thompson Reuters MarketScan; Medicare; Medicaid; and the Clinical Outcomes Research Initiative's National Endoscopic Database. We estimated endoscopic use and costs and examined trends in endoscopic procedure. Abdominal pain was the most common GI symptom that prompted a clinic visit (15.9 million visits). Gastroesophageal reflux was the most common GI diagnosis (8.9 million visits). Hospitalizations and mortality from Clostridium difficile infection have doubled in the last 10 years. Acute pancreatitis was the most common reason for hospitalization (274,119 discharges). Colorectal cancer accounted for more than half of all GI cancers and was the leading cause of GI-related mortality (52,394 deaths). There were 6.9 million upper, 11.5 million lower, and 228,000 biliary endoscopies performed in 2009. The total cost for outpatient GI endoscopy examinations was $32.4 billion. GI diseases are a source of substantial morbidity, mortality, and cost in the United States.